Choosing American Colleges from Afar: Chinese Students’ College Choice in the US - Ding, Liang; Li, Siguo; Xue, Yefei (Journal of International Students, 2024)
Chinese students studying abroad have been increasing rapidly in the past decades and become a significant financial contribution to receiving countries. Accordingly, understanding their enrollment choice is essential to facilitate college marketing and admission strategies. Though the decision process is believed to be different from domestic students, empirical analysis on Chinese students’ enrollment choice is still lacking. This paper fills the void by examining the influential factors of Chinese students’ enrollment choice with novel student-level data. We find that in addition to factors domestic students typically consider, Chinese students particularly emphasize college ranking, reputation, and location in their decision process. Furthermore, unlike domestic students usually preferring colleges with proximity to home, Chinese students’ location preference is linked to job prosperity. We also find that the impact of the factors varies for students from different regions of China, which can be attributable to uneven economic development within the country.